Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. The reality of employing educational technologies in teaching students with disabilities from the point of view of teachers of special educationMr. Abdulrahman Khalaf Aldhafeeri2. The role of the child’s theater in promoting national identity in early childhood according to the Kingdom’s vision 2030 from the point of view of teachersMrs. Atheer Khudhayr Alharbi3. The educational role of intellectual awareness units in Saudi universities in achieving intellectual immunity for its studentsMrs. Retal Muhammad Asiri4. Administrative empowerment among females’ leaders in secondary schools in Hafr Al-Batin and its social, cultural and environmental challengesMrs. Mona Mutlaq Alanazi5. The effectiveness of a proposed program based on communicative theory in teaching Arabic to develop digital intelligence skills for primary school students in Bisha GovernorateProf. Mahmoud Helal Abdelkader, Dr. Edrees Ali Matary6. The reality of female high school principals exercising the dimensions of creative leadership in the governorate of one of the theaters "case study"Mrs. Ayshah Mahah Safhi7. The relationship of academic resilience with positive thinking among female students at King Saud UniversityDr. Aeshah Mohammad Al-Khelaiwi, Co-Prof. Afaf Salem Al-Mohammadi
Keywords: Journal of Educational and Psychological Sciences